1988
DOI: 10.1017/s0033291700008370
|View full text |Cite
|
Sign up to set email alerts
|

Autobiographical memory in depression

Abstract: SYNOPSIS Recent research has shown that suicidal patients are not only biased in the speed with which they can remember positive and negative events from their past, but that they also find it more difficult to be specific in their memories. That is, they tend to recall sequences of events, or time periods, rather than single episodes. This tendency has been found to be more evident with positive than with negative events. This paper examines whether the same phenomenon can be observed in patients with a diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
240
3
9

Year Published

1997
1997
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 345 publications
(281 citation statements)
references
References 17 publications
29
240
3
9
Order By: Relevance
“…Our finding that cue-word valence does not affect the numbers of specific memories retrieved or the retrieval latencies is consistent with some (e.g., Brittlebank et al, 1993;Kuyken & Brewin, 1995;Kuyken & Dalgleish, 1995) but not all (e.g., Puffet et al, 1991;Williams & Dritschel, 1988;Williams & Scott, 1988) previous studies in this area. Early studies found that depressed individuals showed slowed recall and more overgeneral recall in the positive cue-word condition (Puffet et al, 1991;Williams & Dritschel, 1988;Williams & Scott, 1988).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our finding that cue-word valence does not affect the numbers of specific memories retrieved or the retrieval latencies is consistent with some (e.g., Brittlebank et al, 1993;Kuyken & Brewin, 1995;Kuyken & Dalgleish, 1995) but not all (e.g., Puffet et al, 1991;Williams & Dritschel, 1988;Williams & Scott, 1988) previous studies in this area. Early studies found that depressed individuals showed slowed recall and more overgeneral recall in the positive cue-word condition (Puffet et al, 1991;Williams & Dritschel, 1988;Williams & Scott, 1988).…”
Section: Discussionsupporting
confidence: 92%
“…For example, in relation to the cue word 'safe', the response 'I feel safe when I'm in bed' is an overgeneral memory. Findings using this and other methods have shown that cueword valence does not always affect the number and latency of specific memories retrieved (Brittlebank et al, 1993;Kuyken & Brewin, 1995;Kuyken & Dalgleish, 1995;Puffet, JehinMarchot, Timsit-Berthier & Timsit, 1991;Williams & Dritschel, 1988;Williams & Scott, 1988). …”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…This phenomenon of overgeneral recall does not pertain to the content of autobiographical memory, but to its lack of spatiotemporal specificity. Overgeneral recall is associated with a diagnosis of major depression [2][3][4][5] and trauma-related disorders such as acute stress disorder and post-traumatic stress disorder. 6,7 Overgeneral recall is not found in patients with a variety of other psychiatric diagnoses 5,8,9 and normal individuals who score high on neuroticism and/or trait anxiety.…”
mentioning
confidence: 99%
“…É descrito que pacientes deprimidos teriam maior seletividade na evocação de material negativo [49][50] . Williams et al 51 sugerem que o processamento cognitivo ocorreria em dois tempos: um pré-atentivo (que segue a captura atentiva da informação e é refletido em testes de memória implícita) e outro elaborativo (que envolve a associação de informações-alvo com outras informações na memória, refletida em testes explícitos). Se a memória implícita não é comprometida, a memória congruente com o humor será expressa em testes de memória explícita.…”
Section: Memóriaunclassified